Factors affecting willingness to pay for community based health insurance among secondary school teachers of Katsina State, Nigeria - Ahmad Falaki, Ruqayya; Juni, Muhamad Hanafiah; Abdul Manaf, Rosliza (Community Health Society Malaysia, 2017)
Introduction: Universal health coverage is a major challenge in Nigeria where out of pocket payments still dominates health care financing. The community based health insurance scheme was introduced in Nigeria through the National health insurance scheme as an alternative means of financing health care especially for the rural poor and low income earners. The objective of this study is to assess the willingness of secondary school teachers of Katsina Local Government Area to pay for this community based insurance scheme. Methodology: This is cross-sectional study was conducted among secondary school teachers of Katsina local government area of Katsina State using cluster random sampling technique. A self-administered questionnaire which consisted of the Contingent Valuation method for evaluating the WTP for the community based health insurance scheme was used in this study. Results: The response rate was 88.4%. The mean age of the respondent’s was 36.32±7.58 years. More than 62% of the respondents were males, almost half of the respondents 44.1% (n=208) have a family size of 6 to 10 family members. Mean monthly income of respondents was ₦39,192.03± ₦10,900.99. The results indicated that minimum amount the respondents were willing to pay was ₦200 and the maximum was ₦5000. The predictors of willing to pay for the CBHI were ages 41 to 50 years (AOR=0.313; 95%CI: 0.149-0.655), 51 to 60 years (AOR=119; 95%CI: 0.039-0.366) and recent illness encountered (AOR=24.954; 95%CI: 7.581-82.135). Conclusion: In conclusion, our study findings suggest that majority of the respondents were willing to enrol and pay for the CBHI scheme and to pay an average of ₦1585 per month.